Correlation Between Humphrey Visual Field, Optical Coherence Tomography and Heidelberg Retina Tomograph Parameters in Primary Open-Angle Glaucoma, Normal-Tension Glaucoma and Ocular Hypertension - Ziya Ayhan; Gül Ar›kan; Üzeyir Günenç; Güray Ç›ng›l (Türk Oftalmoloji Dergisi, 2011)
Purpose: To evaluate the correlation of Humphrey visual field (VF) parameters (MD and PSD) with Heidelberg Retina Tomograph (HRT) 3 and Stratus optical coherence tomography (OCT) parameters in patients with primary open-angle glaucoma (POAG), normal-tension glaucoma (NTG) and ocular hypertension (OHT). Material and Method: Fifty-five eyes of 29 POAG patients, 32 eyes of 16 OHT patients and 26 eyes of 13 NTG patients were enrolled in the study prospectively. Humphrey visual field test as well as optic nerve head and retinal nerve fiber layer (RNFL) thickness analysis with HRT 3 and Stratus OCT were performed in all patients; the measurements were repeated every 6 months. Results: The mean age of the patients was 66.4±10.0 years and the mean follow-up time was 22±2.2 months. In POAG and NTG groups, MD and PSD correlated with all analyzed parameters in HRT, except for the height variation contour (HVC). In POAG group, MD and PSD values correlated with all analyzed parameters in OCT, except for the rim area (RA). In NTG group, correlation was found between MD values and all parameters in OCT. In NTG group, PSD correlated with all parameters in OCT, except for the RNFL thickness. In OHT group, no correlation was found between MD, PSD values and HRT parameters. In OHT group, only RA values in OCT correlated with MD and PSD. In all groups, there was no statistically significant difference between the first and last examinations for MD and PSD values and for the mean RNFL thickness measured with OCT and HRT. Discussion: In our study, it was found that in POAG and NTG patients, there was a general correlation of Humphrey VF parameters with HRT 3 and Stratus OCT parameters. (Turk J Ophthalmol 2011; 41: 143-50)